Urban Renewal Through Effective Circulation System: A Case Study of Kobape, Ogun State, Nigeria - Oluwagbemisola A. Odularu; Gabriel Olaoye; Engr Obianuju Chukwuka (Britain International for Academic Research (BIAR) Publisher, 2026)
Rapid urbanisation in Nigeria’s peri-urban regions has intensified infrastructure deficits, resulting in fragmented development, limited accessibility, and persistent housing challenges. Although urban renewal is widely adopted as a response, it often overlooks the structural role of circulation systems in shaping urban form. This study examines how road network configuration influences urban renewal patterns in Kobape, Ogun State. A mixed-methods approach combining GIS-based network analysis, field observations, and policy review was employed. Network performance was evaluated using graph-theoretic metrics, including intersection density, link-node ratio, gamma index, and centrality measures. Results reveal a structurally imbalanced network with low connectivity (intersection density: 4.2 junctions/km²; link-node ratio: 1.18; gamma index: 0.41) and high dependence on a single arterial corridor (betweenness centrality: 0.78). This has produced corridor-dominated development, with growth concentrated along the expressway and limited integration of interior areas. The study establishes that connectivity rather than infrastructure provision alone determines urban renewal outcomes. It proposes a connectivity-centred framework emphasising hierarchical networks and internal integration to support equitable and sustainable urban development.